Burkina Faso : Second Review Under the Extended Credit Facility Arrangement and Request for Waiver of Nonobservance of a Performance Criterion-Press Release; Staff Report; and Statement by the Executive Director for Burkina Faso. (IMF Staff Country Reports; Country Report ;, 2019)
In light of widespread concern about the security crisis and protracted public sector pay disputes, the government resigned in January 2019. The new government, installed with a mission to combat the security crisis with more vigor, remains under tremendous pressure. Growth in 2018 remained resilient as a bumper harvest more than compensated for a decline in non-agricultural GDP growth. Inflation remained subdued, and the overall fiscal deficit declined below 5 percent of GDP, though essentially at the cost of lower public investment. Given difficulties in moving ahead with a constitutional reform, the authorities are now focusing on a two-stage strategy to contain the wage bill. First, in the near term, transitional measures will be implemented and the outlook for the wage bill would remain in line with the understandings reached at the first review. Second, in the meanwhile, the authorities will continue exploring politically feasible ways to adopt their reform package. The main risks to the program stem from heightened security risks and further labor disputes.